2023
DOI: 10.3390/ma16114045
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carbonated Bottom Slag Granules in 3D Concrete Printing

Abstract: This study investigates the possibility of utilising bottom slag (BS) waste from landfills, and a carbonation process advantageous for the use of artificial aggregates (AAs) in printed three-dimensional (3D) concrete composites. In general, the main idea of granulated aggregates is to reduce the amount of CO2 emissions of printed 3D concrete objects (wall). AAs are made from construction materials, both granulated and carbonated. Granules are made from a combination of binder (ordinary Portland cement (OPC), h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Carbonization treatment, as another promising method for mortar enhancement, has been extensively investigated during the past decades [ 67 ]. Calcium hydroxide (CH) with high CO 2 -reactivity is prone to precipitating calcium silicate in mortar [ 68 ], which increases the total volume of the mortar by 3%, thus densifying the mortar and improving the properties of RA [ 69 ]. Actually, CH is prone to natural reaction during the service of the parent concrete.…”
Section: Enhancement Methods For Racmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonization treatment, as another promising method for mortar enhancement, has been extensively investigated during the past decades [ 67 ]. Calcium hydroxide (CH) with high CO 2 -reactivity is prone to precipitating calcium silicate in mortar [ 68 ], which increases the total volume of the mortar by 3%, thus densifying the mortar and improving the properties of RA [ 69 ]. Actually, CH is prone to natural reaction during the service of the parent concrete.…”
Section: Enhancement Methods For Racmentioning
confidence: 99%
“…Although a large number of studies have been reported on the influence of carbonization conditions (such as temperature, humidity, etc.) on the carbonization rate [ 69 , 80 , 81 ], the relationship between the phase of the carbonization product, carbonization conditions, and carbonization rate has not been fully studied.…”
Section: Enhancement Methods For Racmentioning
confidence: 99%
“…Ordinary Portland cement (OPC) is the most commonly used binder material, and its extraction and production processes are associated with high energy consumption and significant CO 2 emissions [ 12 , 13 , 14 ], exacerbating global warming issues. Therefore, in the quest to develop cleaner, greener, and more sustainable 3D printing materials, recent research trends have tended towards the use of low-carbon, green binder materials, in order to reduce cement use and carbon dioxide emissions [ 15 , 16 ]. Compared to OPC, geopolymers have been widely accepted as green binders due to their superior mechanical and durability properties [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%